(untitled) (Bangladesh Medical Journal, 2022)
The abuse of methamphetamine, locally known as Yaba locally, has increased in Bangladesh recently. The study was designed to determine the proportion of co-morbidities, in terms of physical, psychiatric and other substances, and family history of substance use and other psychiatric disorders among methamphetamine abusers in Bangladesh.This was a cross-sectional study. Data were collected from the available medical documents of a private hospital dedicated for the management of substance abusers in Dhaka, Bangladesh. Information of the individuals admitted in the hospital during 1 January, 2014 to 31 December, 2015 due to substance related disorders having history of using methamphetamine within one month of hospitalization were enrolled in the study. Completed data of 115 individuals were taken and data analysis was performed using Statistical Package for Social Sciences (SPSS) version 24.Most (91.3%) of the respondents were male. Mean age of the respondents was 24.6 (±5.8) years. Half of the respondents (50.4%) belonged to the age group 21-30 years. Most (89.6%) of them resided in urban area and was Muslim (94.8%). Majority (52.2%) was unmarried. Regarding education status, majority (34.8%) completed graduation. About one-third (33.9%) were currently unemployed. All the methamphetamine users had used other substances. Among the other co-morbid substances, nicotine was the substance used by most (94.8%) respondents, followed by cannabinoids (56.5%) and opiates (38.3%). Among the respondents about one-third (33.9%) had current physical co-morbidities. Co-morbid psychiatric disorders were present among 29.6% of the respondents. Among the respondents, more than one-fourth (27.8%) had family history of substance use, 20.9% had family history of other psychiatric illnesses. All the methamphetamine users had used other substances. A substantial proportion of methamphetamine users had physical and other psychiatric comorbidities and family history of substance and other psychiatric disorders. This essential issue should be considered in the management strategy of methamphetamine use. Bangladesh Med J. 2021 May; 50(2) : 15-20